ANALISIS PERKEMBANGAN SUMBERDAYA LAHAN PERTANIAN DAN KETAHANAN PANGAN DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Syamsiyar, Siti (Caraka Tani: Journal of Sustainable Agriculture, 2008)
The one of development strategy and established of food security in Daerah Istimewa Yogyakarta (DIY) is using food production capacity development that related with optimize of the using of land resources. This effort has a opportunity to success remind that land resources in DIY has wet land as wide as 57.661 hectare and dry land as wide as 260.919 hectare, also un use shore land can be use for agriculture activities. There are many scenarios for to development these, such as 1) wet land and dry land intensification, and rising productivity acceleration of non optimal irrigated wet land, 2) extensification of shore land. Implementation of these scenarios needed supporting to solve technical and non technical problems, like controlling of agriculture land convertion, the wide of agriculture land that tend to limited. As a whole, the handling of land resources heed synergy cooperation inter sector in developing and needed political will from DIY goverment in filling food sufficient trough increasing of food production in DIY.